Officially Supported Export Credits in a Changing World - Wang, Jian-Ye (World Economic and Financial Surveys; World Economic and Financial Surveys ;, 2005)
This paper assesses the issues of government involvement in international trade finance stemming from the recent changes in global financial markets. This study is based on discussions with representatives of export credit agencies during the period from October 2003 to May 2004. A survey of 27 agencies provided valuable insights. Financial flows facilitated by official export credit agencies are large in comparison with official development assistance and gross lending by international financial institutions to developing countries. However, the importance of officially supported trade finance has been declining relative to the rapid expansion of world trade and total capital flows to developing countries. The study highlights the key challenges facing official export credit agencies, including complementing the private sector, facilitating financing to low-income countries while helping maintain these countries' debt sustainability, and playing a positive role in the area of trade finance in international efforts to address emerging market financial crises.